2015
DOI: 10.1002/bip.22705
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the antidiabetic and antilipidemic properties of bacillus subtilis spb1 biosurfactant in alloxan‐induced diabetic rats

Abstract: The present study aimed to scrutinize the potential of Bacillus subtilis SPB1biosurfactant, orally administered, for preventing diabetic complications in rats. The findings revealed that, Bacillus subtilis biosurfactant was an effective reducer of α-amylase activity in the plasma. Moreover, this supplement helped protect the β-cells from death and damage. Both the inhibitory action of SPB1 biosurfactant on α-amylase and the protection of the pancreas' β-cells lead to a decrease of the blood glucose levels, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 58 publications
(62 reference statements)
1
24
0
Order By: Relevance
“…Novel secondary metabolites like lipopeptides, Oxylipins, Limnazine, beta-1,3-1, 4-glucanase are reported from bacillus Sps. (Gond et al, 2015, Trapp et al, 2015, Chen et al, 2013, Asolkar et al, 2002, Zouari et al, 2015, Jin et al, 2011, Liu et al, 2009. Enterobacter cloacae.…”
Section: Discussionmentioning
confidence: 99%
“…Novel secondary metabolites like lipopeptides, Oxylipins, Limnazine, beta-1,3-1, 4-glucanase are reported from bacillus Sps. (Gond et al, 2015, Trapp et al, 2015, Chen et al, 2013, Asolkar et al, 2002, Zouari et al, 2015, Jin et al, 2011, Liu et al, 2009. Enterobacter cloacae.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the therapeutic effect of EPS was recorded due to reduced blood glucose, troponin, total serum cholesterol, LDL, and VLDL as well as suppression of ICAM and VCAM expression. Earlier, Zouari et al (2015) also explored the anti-diabetic and anti-lipidemic properties of biosurfactant produced by B. subtilis SPB1 strain in alloxan induced diabetic rats. Upon oral administration, the biosurfactant reduced the plasma alpha-amylase activity and rendered protection to pancreatic beta cells.…”
Section: Health Benefits Of Probiotic Spore Formersmentioning
confidence: 99%
“…In diabetic group, lipid droplets were observed in the cytoplasm of hepatic and renal tissues, due to the lack of insulin responsible for metabolizing fats. 61 The chemical surfactants are usually used to enhance the solubility and delivery of antidiabetic drugs such as SDS, CTAB and Tween-80. 62 Also, Edwards and his colleagues 63 suggested that using different kind of gums could be effective in reducing postprandial hyperglycemia in human.…”
Section: Inhibition Of A-amylase and A-glucosidasementioning
confidence: 99%